Carboxymethylation of Cassava Peel: Effect Sodium Monochloroacetate and Temperature - Sperisa Distantina; Inayati Inayati; Fahmi Achmad Saputra; Muhammad Fitra Arifianto (Equilibrium Journal of Chemical Engineering, 2018)
Cassava peel contains cellulose that can be chemically modified to be more useful product. In this work, carboxymethylcellulose (CMC) from cassava peel powder was prepared by alkalization using sodium hydroxyde and then followed by carboxymethylation using sodium monochloroacetate. The aims of this work were to investigate the effect of sodium monochloroacetate-powder ratio (0.59, 1.47, 2.95, 4.42) and carboxymethylation temperature (45OC and 70OC) on the degree of substitution (DS) and reaction efficiency (RE).  The  result  of  FTIR  spectra indicated that  carboxylmethyl groups successfully attached on the cellulose backbone to  form CMC structure. The higher of sodium monochloroacetate-powder ratio and higher carboxymethylation temperature enhanced its DS but reduced the RE.